High-gram-weight transfer paper
By using two-component polyurethane adhesive in high-grit transfer paper to form a three-dimensional mesh structure, the problem of insufficient fold resistance of traditional transfer paper is solved, and the fold resistance and scratch resistance of high-grit transfer paper is improved, ensuring that The laser transfer film is firmly adhered to and used for a long time under high temperature and high humidity conditions.
Patent Information
- Application Number
- CN202411514154.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional transfer paper is difficult to take into account both folding and durability in high-weight applications, especially during frequent folding and handling, which cannot meet the needs of high strength and durability, such as the packaging materials of toothpaste boxes.
Two-component polyurethane adhesive is used as the adhesive layer, including components A and components B, which consists of polyether polyol, polyepoxychlorohydrin, vapor phase silica, trimethylolpropane and silane coupling agent It is composed of a three-dimensional mesh structure through cross-linking reaction, which improves the flexibility and adhesion of the adhesive, and enhances the fold resistance and waterproof performance of the paper.
It significantly improves the folding and scratch resistance of high-grain transfer paper. The laser transfer film has good adhesion fastness on the base paper layer, and can maintain good integrity and adhesion under multiple folding and high temperature and high humidity conditions. , extend the service life.
Abstract
Description
Technical Field
[0002] The invention relates to the technical field of aluminized transfer paper, in particular to a high-weight transfer paper. Background Art
[0004] With the increasing awareness of environmental protection, reducing the use of plastics has become a global trend. my country is actively advocating green production and consumption models, encouraging companies to reduce the use of plastic products and promote the application of renewable resources. In this context, seeking new packaging materials that can replace traditional plastic composite materials has become one of the important issues facing many industries. Especially in the field of daily consumer goods, such as toothpaste boxes, the packaging materials of products are facing the need to change from plastic to paper materials.
[0005] As an important paper material, transfer paper is widely used in the packaging industry. However, traditional transfer paper can usually only meet the application requirements of lower weight (such as 250g and below), such as the packaging of cigarette packs. This type of low-weight transfer paper can meet the requirements of most applications in terms of folding resistance and other physical properties. However, for products that require higher strength and durability, such as toothpaste boxes, 300-400g laser paper or composite paper is more commonly used. Although these high-weight papers provide better protection, due to their material characteristics, it is often difficult to take into account good folding resistance, especially during frequent folding and handling. Problems such as breakage are prone to occur.
[0006] In order to respond to national environmental protection policies and achieve the goal of de-plasticizing packaging materials, it is particularly important to develop a transfer paper that can maintain a high grammage and have excellent folding resistance. Summary of the invention
[0008] The purpose of the present invention is to provide a high-weight transfer paper to solve the technical problems mentioned in the above background technology.
[0009] The technical solution for achieving the purpose of the present invention is:
[0010] A high-weight transfer paper comprises a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, wherein the adhesive layer adopts a two-component polyurethane adhesive, and the two-component polyurethane adhesive comprises a component A and a component B; the raw material components of the component B comprise polyether polyol, polyepichlorohydrin, diisocyanate monomer, fumed silica, trimethylolpropane, and a silane coupling agent.
[0011] Furthermore, the raw material components of the A component include castor oil and diisocyanate monomers.
[0012] Furthermore, the diisocyanate monomer includes any one or more combinations of lysine diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
[0013] Furthermore, the silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0014] Furthermore, the preparation steps of the A component are as follows: add 15 to 25 parts by mass of castor oil into a reactor, dehydrate for 1.5 to 2.5 hours while stirring under a vacuum degree of 0.095 MPa and 115 to 125° C., cool to 68 to 72° C. after dehydration, add 100 parts by mass of diisocyanate monomer, raise the temperature to 78 to 82° C. under nitrogen protection, stir the reaction for 1.8 to 2.2 hours, and then discharge to obtain the A component.
[0015] Furthermore, the preparation steps of the B component are as follows: 16 to 20 parts by weight of polyether polyol and 7 to 9 parts by weight of polyepichlorohydrin are placed in a reaction kettle, and dehydrated for 1.5 to 2.5 hours under a vacuum degree of 0.095 MPa and a temperature of 115 to 125° C. while stirring, and after dehydration, the temperature is lowered to 68 to 72° C., 100 parts by weight of diisocyanate monomer is added, and the temperature is raised to 78 to 82° C. under nitrogen protection, and the reaction is stirred for 1.8 to 2.2 hours, and then 90 to 110 parts by weight of fumed silica and 10 to 30 parts by weight of trimethylolpropane are added, and the fumed silica is uniformly dispersed at 800 to 1200 rpm, and the temperature is lowered to 0.095 MPa under a vacuum degree of 115 to 125° C., and the reaction is stirred for 1.8 to 2.2 hours. MPa and 115-125°C, dehydrate with stirring for 1.5-2.5h, cool naturally to 38-42°C, add 118-122 parts by weight of silane coupling agent, heat to 48-52°C, react with stirring for 0.4-0.6h, discharge, and obtain component B.
[0016] Furthermore, the preparation steps of the two-component polyurethane adhesive are as follows: after mixing component A and component B in a mass ratio of 1:3.5-4.5, adding 0.04%-0.08% of a catalyst, stirring evenly, to obtain a two-component polyurethane adhesive.
[0017] Furthermore, the catalyst is dibutyltin dilaurate.
[0018] Furthermore, the base paper layer has a grammage of 300-400 g / m 2 .
[0019] By adopting the above technical solution, the present invention has the following beneficial effects:
[0020] (1) The high-weight transfer paper of the present invention comprises a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, wherein the adhesive layer adopts a two-component polyurethane adhesive, and the two-component polyurethane adhesive comprises a component A and a component B; the raw material components of the component B comprise polyether polyol, polyepichlorohydrin, diisocyanate monomer, fumed silica, trimethylolpropane, and a silane coupling agent; the raw material components of the component A comprise castor oil and diisocyanate monomer; the high-weight transfer paper of the present invention has good folding resistance and scratch resistance, and the laser transfer film has good adhesion strength on the base paper layer.
[0021] (2) The raw material components of component B of the present invention are polyether polyol, polyepichlorohydrin, diisocyanate monomer, fumed silica, trimethylolpropane, and silane coupling agent; wherein the unpolymerized epoxy groups in polyepichlorohydrin (ECP) can undergo cross-linking reaction with polyether polyol and diisocyanate monomer to form a three-dimensional network structure, effectively dispersing stress, improving the flexibility of the adhesive and the folding resistance of the paper, so that the paper can still maintain good integrity after multiple foldings; at the same time, the epoxy groups of ECP can react with water molecules to form stable chemical bonds, reduce the water absorption of the adhesive, and improve its waterproof performance, thereby keeping the paper dry and stable in a high humidity environment and extending its service life; in addition, the epoxy groups in ECP can also react with hydroxyl groups or other active groups on the surface of the paper to form covalent bonds, thereby enhancing the bonding force between the adhesive and the paper, improving its adhesion and durability under high temperature and high humidity conditions, and ensuring that the laser transfer film can still be firmly attached to the surface of the paper after long-term use.
[0022] (3) Trimethylolpropane is introduced into the raw material components of component B of the present invention. As a multifunctional alcohol, trimethylolpropane has three hydroxyl groups and can react with diisocyanate monomers to form multiple cross-linking points to construct a more complex three-dimensional network structure. This structure can effectively disperse stress, improve the flexibility of the adhesive, make the molecular chain of the adhesive more flexible, better adapt to the deformation of paper during folding and bending, reduce the risk of breakage due to excessive rigidity, and significantly improve the folding resistance of paper; in addition, the multiple hydroxyl groups in TMP can chemically react with the hydroxyl groups or other active groups on the surface of paper to form covalent bonds, thereby enhancing the bonding strength between the adhesive and the paper, providing more contact points, increasing the contact area between the adhesive and the surface of the paper, and further improving the bonding strength, so that it can still maintain good adhesion under high temperature and high humidity conditions, and improve its durability, ensuring that the laser transfer film can still be firmly attached to the surface of paper after long-term use.
[0023] (4) The raw material components of component B of the present invention introduce fumed silica and silane coupling agent, wherein fumed silica is a nanometer-scale inorganic filler with extremely high specific surface area and good dispersibility, and can be evenly distributed in the adhesive matrix to form physical crosslinking points, thereby increasing the rigidity and hardness of the adhesive, significantly improving its scratch resistance and surface hardness, making it less susceptible to scratching or abrasion in actual use, and enhancing its overall mechanical properties, making it more stable when subjected to external forces; silane coupling agent is a compound with a bifunctional group, one end of which can be bonded to fumed silica. The hydroxyl group on the surface of silica can react with the other end, and the other end can react with polyurethane to form a chemical bond, which can significantly improve the compatibility of inorganic fillers and organic polymers, improve the dispersibility and stability of fillers in the adhesive matrix, avoid filler agglomeration, enhance the adhesion between the adhesive and the paper surface, and improve its adhesion under high temperature and high humidity conditions, ensuring that the laser transfer film can still be firmly attached to the paper surface after long-term use, and improve the durability of the adhesive, so that it can resist the influence of various physical and chemical factors in actual use, and extend the service life of the paper.
[0024] (5) The silane coupling agent used in the present invention is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEPAMS). The amino group of AEPAMS can react with the hydroxyl group on the surface of fumed silica to form a stable chemical bond, thereby improving the compatibility between the filler and the polymer, making it evenly dispersed in the adhesive and avoiding filler agglomeration. At the same time, the chlorine atoms in polyepichlorohydrin (ECP) can react with the secondary amine in AEPAMS to form a quaternary ammonium salt. The quaternary ammonium salt has a strong positive charge and can adsorb the metal layer in the laser transfer film, thereby significantly improving the bonding force between the adhesive and the laser transfer film and ensuring that good adhesion is maintained under high temperature and high humidity conditions. The addition of AEPAMS also improves the durability of the adhesive, enabling it to resist the influence of various physical and chemical factors in actual use and extend the service life of the paper. DETAILED DESCRIPTION
[0026] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0027] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0028] The raw materials of the embodiments and comparative examples of the present invention are as follows:
[0029] The base paper layer and the laser transfer film are both commercially available materials; the base paper layer has a grammage of 300~400g / m 2
[0030] The polyether polyol adopts polyether polyol DL2000;
[0031] (Example 1)
[0032] A high-weight transfer paper comprises a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, wherein the adhesive layer adopts a two-component polyurethane adhesive, and the two-component polyurethane adhesive comprises a component A and a component B; the raw material components of the component B comprise polyether polyol, polyepichlorohydrin, lysine diisocyanate, fumed silica, trimethylolpropane, and a silane coupling agent.
[0033] The raw material components of the A component include castor oil and lysine diisocyanate.
[0034] The silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0035] The preparation steps of the A component are as follows: add 15 parts by mass of castor oil into a reactor, dehydrate for 1.5 hours under a vacuum degree of 0.095 MPa and 115° C. while stirring, cool to 68° C. after dehydration, add 100 parts by mass of diisocyanate monomer, heat to 78° C. under nitrogen protection, stir and react for 1.8 hours, and then discharge to obtain the A component.
[0036] The preparation steps of the B component are as follows: 16 parts by mass of polyether polyol and 7 parts by mass of polyepichlorohydrin are placed in a reaction kettle, and dehydrated for 1.5 hours while stirring at a vacuum degree of 0.095 MPa and 115° C., and cooled to 68° C. after dehydration, and 100 parts by mass of diisocyanate monomer are added, and the temperature is raised to 78° C. under nitrogen protection, and stirred for reaction for 1.8 hours, and then 90 parts by mass of fumed silica and 10 parts by mass of trimethylolpropane are added, and stirred at 800 rpm until the fumed silica is uniformly dispersed, and dehydrated for 1.5 hours while stirring at a vacuum degree of 0.095 MPa and 115° C., and naturally cooled to 38° C., and 118 parts by mass of silane coupling agent are added, and the temperature is raised to 48° C., and the reaction is stirred for 0.4 hours, and the material is discharged to obtain the B component.
[0037] The preparation steps of the two-component polyurethane adhesive are as follows: after mixing component A and component B in a mass ratio of 1:3.5, adding 0.04% of catalyst dibutyltin dilaurate, stirring evenly, and obtaining the two-component polyurethane adhesive.
[0038] Example 2
[0039] A high-weight transfer paper comprises a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, wherein the adhesive layer adopts a two-component polyurethane adhesive, and the two-component polyurethane adhesive comprises a component A and a component B; the raw material components of the component B comprise polyether polyol, polyepichlorohydrin, lysine diisocyanate, fumed silica, trimethylolpropane, and a silane coupling agent.
[0040] The raw material components of the A component include castor oil and lysine diisocyanate.
[0041] The silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0042] The preparation steps of the A component are as follows: add 20 parts by mass of castor oil into a reactor, dehydrate for 2 hours under a vacuum degree of 0.095 MPa and 120° C. while stirring, cool to 70° C. after dehydration, add 100 parts by mass of diisocyanate monomer, heat to 80° C. under nitrogen protection, stir and react for 2 hours, then discharge to obtain the A component.
[0043] The preparation steps of the B component are as follows: 18 parts by weight of polyether polyol and 8 parts by weight of polyepichlorohydrin are placed in a reaction kettle, and dehydrated for 2 hours while stirring at a vacuum degree of 0.095 MPa and 120° C. After dehydration, the temperature is lowered to 70° C., 100 parts by weight of diisocyanate monomer is added, the temperature is raised to 80° C. under nitrogen protection, and the reaction is stirred for 2 hours, and then 100 parts by weight of fumed silica and 20 parts by weight of trimethylolpropane are added, and the fumed silica is stirred at 1000 rpm until the fumed silica is uniformly dispersed, and the fumed silica is dehydrated for 2 hours while stirring at a vacuum degree of 0.095 MPa and 120° C., and the mixture is naturally cooled to 40° C., 120 parts by weight of silane coupling agent is added, the temperature is raised to 50° C., the reaction is stirred for 0.5 hours, and the material is discharged to obtain the B component.
[0044] The preparation steps of the two-component polyurethane adhesive are as follows: after mixing component A and component B in a mass ratio of 1:4, adding 0.06% of a catalyst dibutyltin dilaurate, stirring evenly, and obtaining the two-component polyurethane adhesive.
[0045] Example 3
[0046] A high-weight transfer paper comprises a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, wherein the adhesive layer adopts a two-component polyurethane adhesive, and the two-component polyurethane adhesive comprises a component A and a component B; the raw material components of the component B comprise polyether polyol, polyepichlorohydrin, diisocyanate monomer, fumed silica, trimethylolpropane, and a silane coupling agent.
[0047] Furthermore, the raw material components of the A component include castor oil and diisocyanate monomers.
[0048] Furthermore, the diisocyanate monomer includes any one or more combinations of lysine diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
[0049] Furthermore, the silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0050] Furthermore, the preparation steps of the A component are as follows: 25 parts by mass of castor oil are placed in a reactor, and dehydrated for 2.5 hours under a vacuum degree of 0.095 MPa and 125° C. while stirring, and after dehydration, the temperature is lowered to 72° C., 100 parts by mass of diisocyanate monomer are added, and the temperature is raised to 82° C. under nitrogen protection, and the reaction is stirred for 2.2 hours before discharging to obtain the A component.
[0051] Furthermore, the preparation steps of the B component are as follows: 20 parts by mass of polyether polyol and 9 parts by mass of polyepichlorohydrin are placed in a reactor, and dehydrated for 2.5 hours while stirring at a vacuum degree of 0.095 MPa and 125°C. After dehydration, the temperature is lowered to 72°C, 100 parts by mass of diisocyanate monomer is added, and the temperature is raised to 82°C under nitrogen protection, and the reaction is stirred for 2.2 hours. Then, 110 parts by mass of fumed silica and 30 parts by mass of trimethylolpropane are added, and the fumed silica is stirred at 1200 rpm until the fumed silica is evenly dispersed, and the fumed silica is dehydrated for 2.5 hours while stirring at a vacuum degree of 0.095 MPa and 125°C. Naturally cool to 42°C, 122 parts by mass of silane coupling agent are added, the temperature is raised to 52°C, the reaction is stirred for 0.6 hours, and the material is discharged to obtain the B component.
[0052] Furthermore, the preparation steps of the two-component polyurethane adhesive are as follows: after mixing component A and component B in a mass ratio of 1:4.5, adding 0.08% of a catalyst, stirring evenly, to obtain a two-component polyurethane adhesive.
[0053] Furthermore, the catalyst is dibutyltin dilaurate.
[0054] Comparative Example 1
[0055] The difference between Comparative Example 1 and Example 2 is that the raw material components of component B only use polyether polyol, lysine diisocyanate, fumed silica, trimethylolpropane, and silane coupling agent, and the remaining steps and components are the same as those of Example 2.
[0056] Comparative Example 2
[0057] The difference between Comparative Example 2 and Example 2 is that the raw material components of component B only use polyether polyol, polyepichlorohydrin, lysine diisocyanate, trimethylolpropane, and silane coupling agent, and the remaining steps and components are the same as those of Example 2.
[0058] Comparative Example 3
[0059] The difference between Comparative Example 3 and Example 2 is that the raw material components of component B only use polyether polyol, polyepichlorohydrin, lysine diisocyanate, fumed silica, and trimethylolpropane, and the remaining steps and components are the same as those of Example 2.
[0060] Comparative Example 4
[0061] The difference between Comparative Example 4 and Example 2 is that the silane coupling agent used is silane coupling agent KH550; the remaining steps and components are the same as those of Example 2.
[0062] Comparative Example 5
[0063] The difference between Comparative Example 5 and Example 2 is that the raw material components of component B include polyether polyol, polyepichlorohydrin, lysine diisocyanate, fumed silica, 1,4-butanediol, and a silane coupling agent; the remaining steps and components are the same as those of Example 2.
[0064] Effect example
[0065] The following table shows the performance data of the high-weight transfer paper prepared in Examples 1 to 3 and Comparative Examples 1 to 5:
[0066] Adhesion strength (3M tape test) Folding resistance Example 1 No shedding 28 times without oral sex Example 2 No shedding 30 times without oral sex Example 3 No shedding 26 times without oral sex Comparative Example 1 Shedding area 4% 19 times without oral sex Comparative Example 2 No shedding 28 times without oral sex Comparative Example 3 26% loss 6 times without oral sex Comparative Example 4 Shedding area 4% 18 times without oral sex Comparative Example 5 Shedding area 2% 22 times without oral sex
[0067] From the comparison of the data of the embodiment and the comparative example in the above table, it can be seen that the high-weight transfer paper prepared in the embodiment has better folding resistance, and the laser transfer film has better adhesion strength on the base paper layer.
[0068] The difference between Comparative Example 1 and Example 2 is that Example 2 uses polyepichlorohydrin, and the unpolymerized epoxy groups in epichlorohydrin (ECP) can undergo cross-linking reactions with polyether polyols and diisocyanate monomers to form a three-dimensional network structure, effectively dispersing stress, improving the flexibility of the adhesive and the folding resistance of the paper, so that it can still maintain good integrity after multiple foldings; in addition, the epoxy groups in ECP can also react with hydroxyl groups or other active groups on the surface of the paper to form covalent bonds, thereby enhancing the bonding force between the adhesive and the paper, improving its adhesion and durability under high temperature and high humidity conditions, and ensuring that the laser transfer film can still be firmly attached to the surface of the paper after long-term use; the chlorine atoms in polyepichlorohydrin (ECP) can react with the secondary amines in the silane coupling agent to form quaternary ammonium salts, which have a strong positive charge and can adsorb the metal layer in the laser transfer film, significantly improving the bonding force between the adhesive and the laser transfer film, and ensuring that good adhesion can be maintained under high temperature and high humidity conditions.
[0069] The difference between Comparative Examples 2 to 4 and Example 2 is that Example 2 uses fumed silica and a silane coupling agent, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane. Fumed silica is a nanoscale inorganic filler with an extremely high specific surface area and good dispersibility. It can be evenly distributed in the adhesive matrix to form physical crosslinking points, increase the rigidity and hardness of the adhesive, and significantly improve its scratch resistance and surface hardness, making it less likely to be scratched or worn in actual use, and enhance its overall mechanical properties, making it more stable when subjected to external forces; the silane coupling agent is a compound with a bifunctional group, one One end can react with the hydroxyl group on the surface of fumed silica, and the other end can react with polyurethane to form a chemical bond, which can significantly improve the compatibility of inorganic fillers and organic polymers, improve the dispersibility and stability of fillers in the adhesive matrix, avoid filler agglomeration, and enhance the adhesion between the adhesive and the paper surface. The chlorine atoms in polyepichlorohydrin (ECP) can react with the secondary amines in the silane coupling agent to form quaternary ammonium salts. Quaternary ammonium salts have a strong positive charge and can adsorb the metal layer in the laser transfer film, significantly improving the adhesion between the adhesive and the laser transfer film, ensuring good adhesion under high temperature and high humidity conditions.
[0070] The difference between Comparative Example 5 and Example 2 is that Example 2 introduces trimethylolpropane. Trimethylolpropane has three hydroxyl groups and can react with diisocyanate monomers to form multiple cross-linking points to construct a more complex three-dimensional network structure. This structure can effectively disperse stress, improve the flexibility of the adhesive, make the molecular chain of the adhesive more flexible, better adapt to the deformation of paper during folding and bending, reduce the risk of breakage due to excessive rigidity, and significantly improve the folding resistance of paper; in addition, the multiple hydroxyl groups in TMP can chemically react with the hydroxyl groups or other active groups on the surface of the paper to form covalent bonds, thereby enhancing the bonding strength between the adhesive and the paper, providing more contact points, increasing the contact area between the adhesive and the surface of the paper, and further improving the bonding strength, so that it can still maintain good adhesion under high temperature and high humidity conditions, and improve its durability, ensuring that the laser transfer film can still be firmly attached to the surface of the paper after long-term use.
[0071] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-weight transfer paper, comprising a base paper layer, a laser transfer film, and an adhesive layer bonded between the base paper layer and the laser transfer film, characterized in that: The adhesive layer adopts a two-component polyurethane adhesive, which includes a component A and a component B; the raw materials of the component B include polyether polyol, polyepichlorohydrin, diisocyanate monomer, fumed silica, trimethylolpropane, and a silane coupling agent.
2. The high-weight transfer paper according to claim 1, characterized in that: The raw material components of the A component include castor oil and diisocyanate monomers.
3. The high-weight transfer paper according to claim 2, characterized in that: The diisocyanate monomer includes any one or more combinations of lysine diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
4. The high-weight transfer paper according to claim 1, characterized in that: The silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
5. The high-weight transfer paper according to claim 2, characterized in that: The preparation steps of the component A are as follows: add 15 to 25 parts by mass of castor oil into a reactor, dehydrate for 1.5 to 2.5 hours under a vacuum degree of 0.095 MPa and a temperature of 115 to 125° C. while stirring, cool to 68 to 72° C. after dehydration, add 100 parts by mass of diisocyanate monomer, heat to 78 to 82° C. under nitrogen protection, stir and react for 1.8 to 2.2 hours, and then discharge to obtain component A.
6. The high-weight transfer paper according to claim 1, characterized in that: The preparation steps of the B component are as follows: 16-20 parts by weight of polyether polyol and 7-9 parts by weight of polyepichlorohydrin are placed in a reaction kettle, and dehydrated for 1.5-2.5 hours while stirring at a vacuum degree of 0.095 MPa and 115-125° C., and after dehydration, the temperature is lowered to 68-72° C., 100 parts by weight of diisocyanate monomer is added, and the temperature is raised to 78-82° C. under nitrogen protection, and the reaction is stirred for 1.8-2.2 hours, and then 90-110 parts by weight of fumed silica and 10-30 parts by weight of trimethylolpropane are added, and the fumed silica is evenly dispersed at 800-1200 rpm, and the vacuum degree is 0.095 MPa and 115-125°C, dehydrate with stirring for 1.5-2.5h, cool naturally to 38-42°C, add 118-122 parts by weight of silane coupling agent, heat to 48-52°C, react with stirring for 0.4-0.6h, discharge, and obtain component B.
7. The high-weight transfer paper according to claim 1, characterized in that: The preparation steps of the two-component polyurethane adhesive are as follows: after mixing component A and component B in a mass ratio of 1:3.5-4.5, adding 0.04%-0.08% of a catalyst, stirring evenly, and obtaining the two-component polyurethane adhesive.
8. The high-weight transfer paper according to claim 7, characterized in that: The catalyst is dibutyltin dilaurate.
Citation Information
Cited By
Platinum embossment aluminum plating transfer paper for plastic removal of wine bag and preparation process of platinum embossment aluminum plating transfer paper
CN120700735A